Botryllin, a Novel Antimicrobial Peptide from the Colonial Ascidian Botryllus schlosseri - Nicola Franchi; Loriano Ballarin; Francesca Cima (Marine Drugs, 2023)
By mining the transcriptome of the colonial ascidian Botryllus schlosseri, we identified a transcript for a novel styelin-like antimicrobial peptide, which we named botryllin. The gene is constitutively transcribed by circulating cytotoxic morula cells (MCs) as a pre-propeptide that is then cleaved to mature peptide. The synthetic peptide, obtained from in silico translation of the transcript, shows robust killing activity of bacterial and unicellular yeast cells, causing breakages of both the plasma membrane and the cell wall. Specific monoclonal antibodies were raised against the epitopes of the putative amino acid sequence of the propeptide and the mature peptide; in both cases, they label the MC granular content. Upon MC degranulation induced by the presence of nonself, the antibodies recognise the extracellular nets with entrapped bacteria nearby MC remains. The obtained results suggest that the botryllin gene carries the information for the synthesis of an AMP involved in the protection of B. schlosseri from invading foreign cells.